Transformational Leadership and Employees’ Thriving at Work: The Mediating Roles of Challenge-Hindrance Stressors - Lin, Chun pei; Xian, Jialiang; Li, Baixun; Huang, Haimei (Frontiers in Psychology, 2020)
Based on previous research, the conceptual model presenting the interaction between transformational leadership, challenge-hindrance stressors and thriving at work was constructed and used to generate the hypotheses for the study. Data were obtained from 542 questionnaires distributed across different organisations. The participants included ordinary employees, grassroots middle and senior managers from China. The major findings are as follows. First, transformational leadership directly is positively related to challenge stressors and thriving at work. Second, challenge stressors are positively relate to thriving at work, while hindrance stressors are negatively relate to thriving at work. Furthermore, challenge stressors mediate the relationship between transformational leadership and thriving at work. Given these findings, the study examined the moderating effect of supervisor developmental feedback on the relationship between transformational leadership and thriving at work. Results reveal that supervisor developmental feedback plays a positive regulatory role between challenge stressors and thriving at work. Additionally, it is shown that the mediating effect of challenge stressors on the relationship between transformational leadership and thriving at work is moderated by supervisor developmental feedback.